A novel homozygous variant extending the peripheral myelin protein 22 by 9 amino acids causes early‐onset Charcot‐Marie‐Tooth disease with predominant severe sensory ataxia. Issue 3 (29th May 2020) - Zambon, Alberto A.; Pitt, Matthew; Laurà, Matilde; Polke, James M.; Reilly, Mary M.; Muntoni, Francesco
Abstract: Peripheral myelin protein 22 (PMP22) related neuropathies account for over 50% of inherited peripheral neuropathies. A gene copy variation results in CMT1A (duplication) and hereditary neuropathy with liability to pressure palsies (HNPP; single deletion). Point mutations comprise both phenotypes. The underlying pathological mechanisms are incompletely understood and biallelic mutations of PMP22 are very rare. We describe a 9‐year‐old girl who presented before the age of 1 year with severe locomotor delay. She now requires support for standing and walking in view of her severe sensory ataxia. Strikingly, her muscle power and bulk are close to normal in all segments. Nerve conduction studies showed sensory‐motor velocities below 5 m/s. Genetic analysis revealed a homozygous sequence change in the PMP22 gene causing the loss of termination codon (c.483A > G; p.[*161Trpext*10]), extending the protein by 9 amino acids. Both heterozygous parents have neurophysiological abnormalities consistent with HNPP, consistent with this being a loss‐of‐function mutation. PMP22‐deficient human models are rare but important to decipher the physiological function of the PMP22 protein in vivo. The predominance of large fiber sensory involvement in this and other rare similar cases suggests a pivotal role played by PMP22 in the embryogenesis of dorsal root ganglia in humans.